Optimalisasi Tingkat Utilitas Gudang Terhadap Jumlah Muatan dan Logistik Pada PT PELNI (Persero) Cabang Batam - Fakhri Syah Putra; R Djayendra Dewa (Logistics and Supply Chain Insights, 2025)
Loading and unloading activities are activities of moving goods from sea transportation to land transportation or vice versa. The problem in this study is that ship delays often occur, resulting in delays in loading and unloading. The objectives of this study are 1) To determine the optimization of receiving and sending goods. 2) To find out how to manage goods so that they are not lost 3) To find out how to check stock so that goods in the warehouse are not damaged. This study uses a qualitative descriptive research method. This research was conducted at PT. Pelayaran Nasional Indonesia (Persero) Batam branch from February to May 2023. The data collection techniques used were observation, interviews, and documentation. While the informants in this study were operational and service staff. The results of this study are: Optimization of receipt and delivery of goods, namely a process to optimize the level of utility for receipt and delivery of goods How to manage goods that are still manual so that there is no loss / damage to goods, namely sufficient storage space because if a warehouse has sufficient storage space, the goods stored in the warehouse are more neatly arranged and give a code to each item The purpose of giving a code to each item is so that there is no mistake in taking the goods available or in the warehouse and Conducting routine recording Routine recording is carried out so that every item that comes out or comes in is always under supervision, so that when checking the goods there is no loss.